Asymmetry in the stock price response to macroeconomic shocks: evidence from the Korean market - Lee, Geul; Ryu, Doojin (Journal of Business Economics and Management, 2018)
This study investigates stock price movements in response to macroeconomic shocks, allowing for asymmetry in this relationship. Given Ferson’s (1989) finding that large and small stocks can exhibit different risk behaviors, we examine the behaviors of the KOSPI and KOSDAQ stock markets in response to changes in the price level, real interest rate, and real USD/KRW exchange rate using simple and nonlinear autoregressive-distributed lag (ARDL) models. We find that the long-run effects of macroeconomic shocks are relatively insignificant under the simple ARDL model, whereas a significant and negative long-run effect is found for almost every explanatory variable–market pair under the nonlinear model. In addition, we find that the long-run effects of stock price shocks on macroeconomic variables are more significant under the nonlinear model. Overall, the results imply that it is difficult to identify the relationship between macroeconomic variables and stock price dynamics without considering asymmetry.